Big data, big analytics : emerging business intelligence and analytic trends for today's businesses - Minelli, Michael, 1974-; Chambers, Michele; Dhiraj, Ambiga, 1975- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
"The availability of Big Data, low-cost commodity hardware and new information management and analytics software has produced a unique moment in the history of business. The convergence of these trends means that we have the capabilities required to analyze astonishing data sets quickly and cost-effectively for the first time in history. These capabilities are neither theoretical nor trivial. They represent a genuine leap forward and a clear opportunity to realize enormous gains in terms of efficiency, productivity, revenue and profitability. The Age of Big Data is here, and these are truly revolutionary times. This timely book looks at cutting-edge companies supporting an exciting new generation of business analytics"--Provided by publisher.
Chapter 1. What is big data and why is it important? -- chapter 2. Industry examples of big data -- chapter 3. Big data technology -- chapter 4. Information management -- chapter 5. Business analytics -- chapter 6. The people part of the equation -- chapter 7. Data privacy and ethics.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Business intelligence; Information technology; Electronic data processing; Data mining; Strategic planning; Business intelligence; Information technology; Business -- Data processing; Data mining; Strategic planning; BUSINESS & ECONOMICS -- Corporate Governance; BUSINESS & ECONOMICS -- Leadership; BUSINESS & ECONOMICS -- Organizational Development; BUSINESS & ECONOMICS -- Workplace Culture; Business intelligence; Data mining; Electronic data processing; Information technology; Strategic planning; Business intelligence; Information technology; Business / Data processing; Data mining; Strategic planning; Electronic books; Electronic books